(untitled) (Revista Latino-Americana de Enfermagem, 2005)
This study aimed to identify the prevalence of different types of breastfeeding and how they relate to maternal variables in the municipality of Conchas, São Paulo, Brazil, which is fully covered by the family health program. We collected information about the current eating habits of children under one year old who were attended during the 2003 Multivaccination Campaign. Associations were submitted to the chi-square test, adopting p